경인아라뱃길이 지역 부동산 가격에 미친 영향 분석 - 이희찬; 차주영; 박두호; Lee, Hee-Chan; Cha, Joo-Young; Park, Doo-Ho (Journal of Korea Water Resources Association, 2013)
The purpose of this research is to evaluate the scenic value of the Gyungin Ara waterway in real estate prices. Apart from the multi-functionality such as transportation of passengers and freight, prevention of floods, and provision of leisure areas, the Ara waterway possesses a scenic function which offers people esthetic value through unique and beautiful scenery. This scenic function is an externality for apartment residents living nearby. The applied methodology for this research is the Hedonic Price Model (HPM) which creates a cause and effect model between real estate prices and attributes. Variables such as apartment sale prices, complex characteristics, location characteristics, timely characteristics have been deduced through data collected from a total of 4,207 households that have experienced actual transactions during the same period, all located within the scenic benefit boundaries of the waterway. Landscape variable has been derived from algorithm designed by a combination of digital map and Google Mapview. The scenic value of the waterway estimated through the application of HPM on these variables is 165,000 Won per area (pyeong). The regional asset enhancing effect caused by the landscape view of the waterway is estimated to be 89.1 billion won. 경인아라뱃길의 경관기능은 조망대상으로써 인근 아파트주민에게는 외부경제효과를 의미한다. 본 연구의 목적은 주택가격에 내재된 아라뱃길 조망권의 가치를 평가하는 것이다. 적용된 방법은 헤도닉가격모형(HPM)이다. 조망 수혜지역 내에 있는 아파트들 중 2011년 기간에 실제 거래가 이루어진 총 4,207세대로부터 수집된 자료를 기반으로 아파트매매가격, 단지특성, 입지특성, 시점특성 등과 관련된 변수들을 도출하였다. 투입 속성으로서 조망권변수는 수치지형도와 Google Mapview의 결합에 의해 고안된 조망권 알고리즘에 의해 도출되었다. 기존에 수행된 주택가격결정모형의 추정결과와 비교해 보았을 때, 본 모형의 추정결과는 계수의 크기에 있어 다소의 차이는 있으나 방향성에 있어서는 일치하는 경향을 보였다. 특히, 주거공간으로부터 아라뱃길까지의 거리와 아라뱃길의 조망권이 주택가격 형성에 있어 중요한 역할을 한다는 점을 밝혔다. HPM에 의해 추정된 조망권의 가치는 평당 16.5만원으로 나타났다. 역내 모집단 아파트로 확장된 아라뱃길 조망권에 의한 지역자산 고도화 효과는 총 891억원으로 추정되었다.